Employee Performance: The Use of Information Technology, Work Motivation, and Work Environment Through Job Satisfaction as An Intervening Variable at Bank Nagari Payakumbuh Branch - Hanum, Ranthika; Veri, Jhon; Lusiana, Lusiana (Journal Research of Social Science, Economics, and Management, 2024)
This research investigates the influence of information technology usage, work motivation, and work environment on employee performance at Bank Nagari's Payakumbuh Branch, with job satisfaction acting as an intervening variable. The study involved distributing questionnaires to 93 employees, and the data was analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings reveal that information technology usage, work motivation, and work environment positively and significantly influence job satisfaction. Furthermore, information technology and job satisfaction directly contribute to enhancing employee performance. Interestingly, while work motivation does not have a direct impact on employee performance, it improves performance indirectly through job satisfaction. On the other hand, the work environment negatively affects employee performance, but its impact turns positive when job satisfaction is included as a mediating factor. These results highlight the essential role of job satisfaction in bridging the relationship between work-related factors and performance outcomes. The study suggests that organizations, particularly in the banking sector, should focus on enhancing job satisfaction by improving work motivation, work environment, and efficient use of information technology to achieve better employee performance.